Novel Design Concepts of Efficient Mg‐Ion Electrolytes toward High‐Performance Magnesium–Selenium and Magnesium–Sulfur Batteries. Issue 11 (17th January 2017) - Zhang, Zhonghua; Cui, Zili; Qiao, Lixin; Guan, Jing; Xu, Huimin; Wang, Xiaogang; Hu, Pu; Du, Huiping; Li, Shizhen; Zhou, Xinhong; Dong, Shanmu; Liu, Zhihong; et al.
Abstract : Developing high‐voltage Mg‐compatible electrolytes (>3.0 V vs Mg) still remains to be the biggest R&D challenge in the area of nonaqueous rechargeable Mg batteries. Here, the key design concepts toward exploring new boron‐based Mg salts in a specific way of highlighting the implications of anions are proposed for the first time. The well‐defined boron‐centered anion‐based magnesium electrolyte (BCM electrolyte) is successfully presented by facile one‐step mixing of tris(2H‐hexafluoroisopropyl) borate and MgF2 in 1, 2‐dimethoxyethane, in which the structures of anions have been thoroughly investigated via mass spectrometry accompanied by NMR and Raman spectra. The first all‐round practical BCM electrolyte fulfills all requirements of easy synthesis, high ionic conductivity, wide potential window (3.5 V vs Mg), compatibility with electrophilic sulfur, and simultaneously noncorrosivity to coin cell assemblies. When utilizing the BCM electrolyte, the fast‐kinetics selenium/carbon (Se/C) cathode achieves the best rate capability and the sulfur/carbon (S/C) cathode exhibits an impressive prolonged cycle life than previously published reports. The BCM electrolyte offers the most promising avenue to eliminate the major roadblocks on the way to high‐voltage Mg batteries and the design concepts can shed light on future exploration directions toward high‐voltage Mg‐compatible electrolytes. Abstract : The well‐designed all‐round practical Mg‐ion electrolyte fulfills all requirements of easy synthesis, high ionic conductivity, wide potential window up to 3.5 V versus Mg, compatibility with high‐capacity selenium and sulfur active materials, and simultaneously noncorrosivity to coin cell assemblies.